2018
DOI: 10.6004/jnccn.2018.7002
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Counseling Referral Rates in Long-Term Survivors of Triple-Negative Breast Cancer

Abstract: Inherited gene mutations (pathogenic variants) cause 10% of breast cancers. pathogenic variants predispose carriers to triple-negative breast cancer (TNBC); around 30% of patients with TNBC carry pathogenic variants. The 2018 NCCN Guidelines for Genetic/Familial High-Risk Assessment: Breast and Ovarian recommend genetic counseling referrals for patients with TNBC diagnosed at age ≤60 years. This study sought to describe genetic counseling referral patterns among long-term TNBC survivors at The University of Te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 26 publications
1
9
0
Order By: Relevance
“…24 There is a possibility that our results are due in part to selection bias, as similar rates of PVs in BRCA genes (31%-35%) have been reported in TNBC patients referred for genetic counseling in the United States. 25,26 However, our group previously observed that 27% of Mexican TNBC patients aged ≤50 years at diagnosis had a BRCA PV, 14 and the results of this study confirm a high rate of BRCA-associated cases in Mexican patients with this molecular subtype. BRCA1 and BRCA2 represented the majority of PVs identified in this cohort.…”
Section: Discussionsupporting
confidence: 70%
“…24 There is a possibility that our results are due in part to selection bias, as similar rates of PVs in BRCA genes (31%-35%) have been reported in TNBC patients referred for genetic counseling in the United States. 25,26 However, our group previously observed that 27% of Mexican TNBC patients aged ≤50 years at diagnosis had a BRCA PV, 14 and the results of this study confirm a high rate of BRCA-associated cases in Mexican patients with this molecular subtype. BRCA1 and BRCA2 represented the majority of PVs identified in this cohort.…”
Section: Discussionsupporting
confidence: 70%
“…Testing rates also vary widely according to BC receptor subtype [104,[113][114][115][116][117][118]. Potential barriers to BRCA testing uptake and genetic counseling for eligible women with or without a diagnosis of BC include: lack of understanding and knowledge about genetic counseling and testing by physicians and patients; lack of perceived benefits of counseling; lack of perceived risk of having a mutation; cost of testing; and fear of insurance discrimination [94,109,[119][120][121]. Patients' attitudes to BRCA testing (the predisposing factor), income (the enabling factor), and risk of carrying a BRCA mutation (the need factor) predict uptake of BRCA testing [122].…”
Section: Issues With Uptake Of Brca Mutation Testingmentioning
confidence: 99%
“…In 2005, it was estimated 12.1% of eligible women with breast cancer received genetic testing . Recent estimates are higher, with estimates as high as 40%‐50%, while other studies report lower testing rates of 20%‐30% . Given the impact of genetic test findings on treatment decisions (type of surgery and chemotherapy, use of PARP inhibitors), our findings emphasize the need to further expand genetic testing among eligible breast cancer patients.…”
Section: Discussionmentioning
confidence: 66%